Analisis Kesadaran, Sertifikasi dan Bahan Makanan Halal Terhadap Minat Beli Produk Makanan di Restoran Jabodetabek - Riko Restu Pradana; Nurizal Ismail (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to examine the influence of halal awareness, halal certification and halal food ingredients on the decision to purchase food products in restaurants in JABODETABEK. his study uses quantitative methods and sampling techniques using purposive sampling. The research instrument is a structured questionnaire with a Likert scale of 1-5. The analysis of this study uses Partial Least Square-Structural Equation Modeling (PLS-SEM) with the help of Smart-PLS 3.0 software on 100 respondents. This article's research shows that halal awareness influences the interest in buying food products in restaurants in JABODETABEK. Halal certification influences the interest in buying food products in restaurants in JABODETABEK. And halal food ingredients also influence the interest in buying food products in restaurants in JABODETABEK.